Conceptual Review Of Raktapitta In Ayurvedic Classics With Modern Correlation To Hemorrhagic Disorders - Dr. Ujjwal; Dr. (Prof.) Basant Kumar Thakur (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Background: Raktapitta is one of the most significant Raktapradoshaja Vikaras described in Ayurvedic literature, characterized by vitiation of Pitta and Rakta Dhatu. It is classified into two primary types: Urdhwaga (upward flow) and Adhoga (downward flow), depending on the route of expulsion of vitiated blood. The disease embodies the pathological interaction of Rakta and Pitta, resulting in hemorrhagic manifestations such as epistaxis, hematemesis, and rectal bleeding. Acharya Charaka, Sushruta, and Vagbhata have extensively discussed its Nidana, Samprapti, and Chikitsa. Aim and Objectives: To review the concept of Raktapitta in Ayurvedic classics. To explore its pathological basis and classifications. To correlate Raktapitta with hemorrhagic disorders in modern medicine. Materials and Methods: A critical review of Charaka Samhita, Sushruta Samhita, Ashtanga Hridaya, and other Nighantus was conducted to extract references on Raktapitta. Modern texts of pathology and hematology were reviewed to find relevant correlations with hemorrhagic disorders. A comparative and interpretative analysis was done to bridge the classical and modern perspectives. Results: The classical description of Raktapitta mirrors the modern understanding of systemic bleeding disorders such as gastrointestinal hemorrhage, epistaxis, hemoptysis, and intracranial bleeding. The role of aggravated Pitta in increasing Rakta Dravata (fluidity) is analogous to mechanisms seen in platelet disorders, coagulopathies, or capillary fragility. Management in Ayurveda includes Shodhana and Shamana therapies using herbs with Rakta-stambhaka, Pitta-shamaka, and Raktaprasadana actions. Discussion: Raktapitta can be seen as a group of disorders rather than a single entity, encompassing various modern hemorrhagic conditions. The Ayurvedic Samprapti provides a unique approach focusing on systemic balance, dietary regulation, and strengthening of vascular integrity. Modern conditions like idiopathic thrombocytopenic purpura (ITP), hemophilia, or vitamin K deficiency-related bleeding show partial symptom overlap. However, Raktapitta’s holistic treatment approach includes Shodhana, Shamana, and Rasayana therapies, which could have potential integrative value. Conclusion: Raktapitta serves as a comprehensive Ayurvedic construct to understand and manage hemorrhagic disorders. Its detailed Samprapti, diagnostic parameters, and therapeutic measures reflect a holistic clinical understanding that can be integrated with modern hematological insights for better patient outcomes.